Foreign Investment in Sustainable Management of Natural Resources in Indonesia - Silalahi, Kristianto P.H. (Law Research Review Quarterly, 2015)
Article 33 paragraph 3 of the 1945 Constitution confirms that the earth, water and natural resources contained therein are controlled by the state and used as much as possible for the prosperity of the people. Therefore, the management of natural resources that control the lives of many people must be managed properly in order to provide optimal benefits for the people of Indonesia. The 1945 Constitution has never banned foreign investment in the management of natural resources in Indonesia and even foreign investment has significantly contributed to boosting the nation's economy. The urge to optimize local potential faced with the demands of opening up in the era of globalization needs to be well regulated so that the presence of multinational companies in the management of natural resources in Indonesia remains effective in providing the greatest prosperity of the people.